A Model for Ranking and Optimization of Key Performance Indicators of the Strategy Process - Gacic, Marija; Nestic, Snezana; Djordjevic Zahar, Marija; Stefanovic, Miladin (International Journal of Industrial Engineering and Management, 2015)
Small and medium sized companies are faced with a series of challenges in order to improve the qualityof their key business processes. Quality management system and the requirements of ISO 9001:2008 are usually reliable when defining the key performance indicators of processes, and the process approach enables monitoring of the process indicators’ effectiveness for the whole organization. Evaluation, monitoring and ranking of key performance indicators can provide quality improvement of strategy process performance in different SMEs. A model based on genetic algorithms has been developed in order to rank key performance indicators of the strategy process. This model can have a great practical use for a company’s management team in the quality assessment of strategy process performance in their company. Article history: Received (01.09.2014.); Revised (29.01.2015.); Accepted (27.02.2015.)